Opinion: We must build food system resilience before the next crisis - Kosec, Katrina; Swinnen, Johan (2023)
In February 2022, news of Russia’s invasion of Ukraine dominated headlines around the world. Policymakers everywhere worried about the potential ripple effects of the invasion on the economic recovery from COVID-19, as well as on political stability — and food and nutrition security. These worries proved to be well-founded: International food prices spiked by nearly a third and fertilizer prices tripled. The conflict erupted at a time of already high uncertainty for food systems. Well before missiles were aimed at Kyiv, many countries, particularly in Africa and the Middle East, were already contending with food crises and high prices. Farmers in South America and Malaysia were struggling with poor harvests, COVID-19 was scrambling supply chain logistics, and consumers, especially in China, were emerging from lockdowns and driving up demand. Gender equality also faced a global decline.